LEARNING-BASED MULTIMEDIA TRAFFIC SIGNS - David Setiyawan; Drs. Sutarno Usna, MMSI (Jurnal Sistem Informasi, 2004)
In scientific writing, the writer will try mebuat an Application of Traffic Signs Based Learning Multimedia, which aims to assist road users, especially for drivers of vehicles, so they are more familiar with traffic signs according to the classification without having read the books but they can see and learn at the same time Visually, these words will help him through the animation that made the author. The discussion starts with how the animation was made to enter data about grammar that is easily understood by users of this program. To clarify the discussion that the author will also describe the software used in applications such as Flash 5.0 which dapay clarify the matter.